2019
DOI: 10.1007/s00109-019-01823-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel plasma peptide markers involved in the pathology of CKD identified using mass spectrometric approach

Abstract: Chronic kidney disease (CKD) may progress to end-stage renal disease (ESRD) at different pace. Early markers of disease progression could facilitate and improve patient management. However, conventional blood and urine chemistry have proven unable to predict the progression of disease at early stages. Therefore, we performed untargeted plasma peptidome analysis to select the peptides involved in progression, which are suitable for long prospective studies in future. The study consists of non-CKD (n = 66) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Since LMWPs are small enough to readily enter the blood from different tissue locations, they are expected to be identified as disease-associated biomarkers. LMWPs have been implicated in various human diseases such as cancer, diabetes, and chronic kidney diseases and represent a treasure trove of diagnostic molecules. For example, the ratio of the amyloid-β precursor protein and amyloid-β fragments can be used for the diagnosis of Alzheimer’s disease …”
Section: Introductionmentioning
confidence: 99%
“…Since LMWPs are small enough to readily enter the blood from different tissue locations, they are expected to be identified as disease-associated biomarkers. LMWPs have been implicated in various human diseases such as cancer, diabetes, and chronic kidney diseases and represent a treasure trove of diagnostic molecules. For example, the ratio of the amyloid-β precursor protein and amyloid-β fragments can be used for the diagnosis of Alzheimer’s disease …”
Section: Introductionmentioning
confidence: 99%
“…Since peptidomics is a powerful tool to discover and determine new biomarkers 23,24 as well as to identify novel peptides to be employed in prevention and prediction models 35 , we developed and applied a work ow to prepare, analyze and interpret peptidomics data by the employment of mass spectrometry and statistics to investigate the plasma of patients suffering from portal hypertension and liver diseases, comparing the molecular pro le before and after TIPS treatment to reduce portal hypertension. The peptidomics approach adopted in this study focused on identifying only features that showed to be signi cantly different between the two groups analysed (before and after TIPS treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Peptidomics is a proteomics-derived branch of omics techniques and is based on liquid chromatographymass spectrometry (LC-MS) as an e cient method for targeted and non-targeted peptide identi cation in diseases 23,24 . LC-MS allows wide-spectrum analyses of the peptidome and metabolome and hence it has been successfully employed for the identi cation of biomarkers of various diseases 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Untargeted analyses are rare in clinical peptidomics but have successfully been used to identify early markers of disease progression for conditions such as chronic kidney disease. 150 Using acid precipitation and fractionation by reverse-phase chromatography, peptides were extracted from plasma from patients with various stages of kidney disease. By also analyzing control samples to generate linear prediction models, new potential biomarkers for the disease were identified.…”
Section: Untargeted Clinical Applicationsmentioning
confidence: 99%